Discrepancies in Work-Family Integration Between Female and Male Orthopaedic Surgeons. (2nd March 2022) - Ponzio, Danielle Y.; Bell, Courtney; Stavrakis, Alexandra; Skibicki, Hope; Czymek, Miranda; Ong, Alvin C.; Post, Zachary D.; Bishop, Meghan E.
Update: This article was updated on March 15, 2022, because of a previous omission of a blurb noting that the online version of the article included supporting material provided by the authors. That blurb, with a link to the supporting material, has been added on page 471. Background: Female surgeons, representing 6.5% of the American Academy of Orthopaedic Surgeons, are particularly vulnerable to work-family conflict. This conflict may deter women from considering orthopaedic surgery as a specialty. The study objective was to identify differences in work-family integration between female and male orthopaedic surgeons in the United States. Methods: An anonymous survey collecting data within the domains of work, family, and satisfaction was completed by 347 orthopaedic surgeons (153 female, 194 male). Differences in responses between males and females were identified. Results: Female surgeons were younger than males (mean, 41.1 versus 50.1 years; p < 0.001) and earlier in their careers, with 60.3% of males in practice >10 years compared with 26.1% of females (p < 0.001). Consulting (7.8% versus 31.4%; p < 0.001), course faculty positions (19.0% versus 39.2%; p < 0.001), and academic and leadership titles (30.7% versus 47.4%; p = 0.002) were significantly less common among females. There was a significant income disparity between females (mean yearly income, 300, 000 to 400, 000) and males (mean, 400, 000 to 500, 000; p < 0.001). Females were more likely to have never married (12.4% versus 2.6%; p < 0.001), or they married at a later mean age (30.2 ± 4.7 versus 28.3 ± 3.9 years; p < 0.001). Females were more likely to have no children (29.4% versus 7.8%; p < 0.001), require fertility treatment (32.0% versus 11.9%; p < 0.001), and not have children until after completing their medical training (63.0% versus 31.1%; p < 0.001). Female surgeons reported more responsibility in parenting (p < 0.001) and household duties (p < 0.001) than males. Work-family balance satisfaction was 72.3% in females and 82.1% in males (p = 0.081). Conclusions: This study highlights deficiencies in work-family integration that appear to uniquely impact female orthopaedic surgeons. Female surgeons delay starting a family, more frequently require fertility treatments, carry more responsibility at home, have fewer academic and leadership roles, earn lower incomes, and are less satisfied with work-family balance relative to males. The discrepancy in work-family integration must be addressed to attract, support, and retain women as successful orthopaedic surgeons.